2022
DOI: 10.1177/0734371x221130977
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Service Workers: The Role of Policy and Management in (Re)shaping Wellbeing for Emergency Service Workers

Abstract: This article examines the impact of psychosocial safety climate (PSC) levels and strength on the job stress and psychological distress of emergency services workers within street level bureaucracies (SLBs). The reason for the research is because the nature of their work and organizational context pre-disposes them to elevated level of psychological distress, and places them at a higher risk of subsequent debilitating physical and mental diseases, which is a cost borne by employees, their families, friends, SLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…Mental health problems are common and often remain untreated, as was also found by scholars analyzing other street-level bureaucrats working during the pandemic (e.g. Brunetto et al, 2022;Farr-Wharton et al, 2022;Salehi et al, 2023). In our cases we found that, in response to untreated mental health issues, workers often develop fatalist or cynical attitudes regarding their work.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Mental health problems are common and often remain untreated, as was also found by scholars analyzing other street-level bureaucrats working during the pandemic (e.g. Brunetto et al, 2022;Farr-Wharton et al, 2022;Salehi et al, 2023). In our cases we found that, in response to untreated mental health issues, workers often develop fatalist or cynical attitudes regarding their work.…”
supporting
confidence: 84%
“…This points to the broader importance of analyzing psychological wellbeing and emotional labor as explanatory factors for frontline worker behavior and policy outcomes (cf. Brunetto et al., 2022; Dudau & Brunetto, 2022; Farr‐Wharton et al., 2022; Ogbonnaya et al., 2023; Varela Castro et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare workers make up one of the highest proportions (18%) of Australian serious workers' compensation claims for mental stress (SafeWork, 2021). Hierarchical bullying is a type of deviant and destructive behaviour that occurs when a supervisor targets an individual or a group of subordinates (Caillier, 2020;Demir & Rodwell, 2012;Farr-Wharton et al, 2022;Norton et al, 2017). Victims are often subjected to ridicule, social isolation, professional undermining, an excessive workload, malicious gossip and the assignment of menial tasks by perpetrators with greater perceived workplace power and authority (De Cieri, Sheehan, Donohue, Shea, & Cooper, 2019;Omari & Paull, 2016).…”
Section: Introductionmentioning
confidence: 99%